Identification of snow ablation rate, ELA, AAR and net mass balance using transient snowline variations on two arctic glaciers - S. H. Mernild; M. Pelto; J. K. Malmros; J. C. Yde; N. T. Knudsen; Edward Hanna (2013)
Identification of the transient snowline (TSL) from high spatial resolution Landsat imagery on Lemon Creek Glacier (LCG), southeast Alaska, USA, and Mittivakkat Gletscher (MG), southeast Greenland, is used to determine snow ablation rates, the equilibrium-line altitude (ELA) and the accumulation-area ratio (AAR). The rate of rise of the TSL during the ablation season on a glacier where the balance gradient is known provides a measure of the snow ablation rate. On both LCG and MG, snow pits were completed in regions that the TSL subsequently transects. This further provides a direct measure of the snow ablation rates for a particular year. TSL observations from multiple dates during the ablation season from 1998 to 2011 at LCG and 1999 to 2012 at MG were used to explore the consistency of the TSL rise and snow ablation rate. On LCG and MG the satellite-derived mean TSL migration rates were 3.8 ±0.6 and 9.4±9.1md-1, respectively. The snow ablation rates were 0.028 ± 0.004 m w.e. d-1 for LCG and 0.051 ±0.018 m w.e. d-1 for MG estimated by applying a TSL-mass-balance-gradient method, and 0.031 ± 0.004 and 0.047 ± 0.019 m w.e. d-1 by applying a snow-pitsatellite method, illustrating significant agreement between the two different approaches for both field sites. Also, satellite-derived ELA and AAR, and estimated net mass-balance (Ba) conditions were in agreement with observed ELA, AAR and Ba conditions for LCG and MG.